Incidence, prevalence and mortality of patients with psoriasis: a U.K. population‐based cohort study. (22nd December 2016) - Springate, D.A.; Parisi, R.; Kontopantelis, E.; Reeves, D.; Griffiths, C.E.M.; Ashcroft, D.M.
Abstract : What's already known about this topic? The burden of psoriasis across many world regions is high and there is a need to better understand the epidemiology of this common skin disorder. What does this study add? The prevalence of psoriasis in the U.K. is increasing and is higher than suggested from previous studies. A key driver to this increase relates to improvements in life expectancy rather than an increase in incidence of psoriasis over time. Despite improvements in life expectancy, patients with psoriasis remain more likely to die prematurely compared with those without psoriasis with no evidence of change in this premature mortality gap. Linked Comment: Cust and Murrell. Br J Dermatol 2017;176 :568–569 . Plain language summary available online Summary: Background: The burden of psoriasis across many world regions is high and there is a recognized need to better understand the epidemiology of this common skin disorder. Objectives: To examine changes in the prevalence and incidence of psoriasis, and mortality rates over a 15‐year period. Methods: Cohort study involving analysis of longitudinal electronic health records between 1999 and 2013 using the U.K. Clinical Practice Research Datalink (CPRD). Results: The prevalence of psoriasis increased steadily from 2·3% (2297 cases per 100 000) in 1999 to 2·8% (2815 per 100 000) in 2013, which does not appear to be attributable to changes in incidence rates. We observed peaks in age bands characteristic of early‐onset (type I) and late‐onset (type II) psoriasis, and changes in incidence and prevalence rates with increasing latitude in the U.K. All‐cause mortality rates for the general population and for patients with psoriasis have decreased over the last 15 years. However, the risk of all‐cause mortality for patients with psoriasis remains elevated compared with people without psoriasis (hazard ratio 1·21; 95% confidence interval 1·13–1·3) and we found no significant change in this relative excess mortality gap over time. Conclusions: We found an increasing population living longer with psoriasis in the U.K., which has important implications for healthcare service delivery and for resource allocation. Importantly, early mortality in patients with psoriasis remains elevated compared with the general population and we found no evidence of change in this premature mortality gap.